Cortical hierarchy disorganization in major depressive disorder and its association with suicidality - Shiwei, Lin; Xiaojing, Zhang; Yingli, Zhang; Shengli, Chen; Xiaoshan, Lin; Ziyun, Xu; Gangqiang, Hou; Yingwei, Qiu (Frontiers in Psychiatry, 2023)
Objectives To explore the suicide risk-specific disruption of cortical hierarchy in major depressive disorder (MDD) patients with diverse suicide risks. Methods Ninety-two MDD patients with diverse suicide risks and 38 matched controls underwent resting-state functional MRI. Connectome gradient analysis and stepwise functional connectivity (SFC) analysis were used to characterize the suicide risk-specific alterations of cortical hierarchy in MDD patients. Results Relative to controls, patients with suicide attempts (SA) had a prominent compression from the sensorimotor system; patients with suicide ideations (SI) had a prominent compression from the higher-level systems; non-suicide patients had a compression from both the sensorimotor system and higher-level systems, although it was less prominent relative to SA and SI patients. SFC analysis further validated this depolarization phenomenon. Conclusion This study revealed MDD patients had suicide risk-specific disruptions of cortical hierarchy, which advance our understanding of the neuromechanisms of suicidality in MDD patients.